Synthesis and Characterization of 3-Formyl-1H-2-benzopyran-1-one - Hussain, Mazhar; Badaruddin Ahmad, Hafiz; Aslam Shad, Muhammad; Hussain, Adeel; Yousaf, Muhammad; Uzair, Muhammad; Shafiq, Zahid (Asian Journal of Chemistry, 2012)
Synthesis and characterization of 3-formyl-1H-2-benzopyran-1-one is reported through convenient three step method. Homophthalic acid and ethyloxalyl chloride were refluxed to afford isocoumarin 3-ethylcarboxylate, which was subsequently heated to reflux with ethanolic hydrazine hydrate to yield isocoumarin-3-hydrazide. The product is treated with ammoniacal solution of metaperiodate to synthesize 3-formyl-1H-2-benzopyran-1-one. All products were characterized by IR, NMR and mass spectral analysis. Physical and spectral data were in close agreement with those, reported in literature.